1964
DOI: 10.1037/h0044571
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of length of stay out of the hospital for released psychiatric patients.

Abstract: The scores of 104 consecutively released nongeriatric psychiatric patients on the California Psychological Inventory, the Waco Social Adequacy Scale, Opinions about Mental Illness Scale (administered to relatives also) and background variables were correlated with success or failure in achieving a 9-month uninterrupted stay in the community after release. Only the Waco, OMI Authoritarianism, Benevolence, and Social Restrictiveness, and 4 of the background variable correlated significantly (p < .10) with the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1967
1967
1990
1990

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…The findings of some of the more recent studies concerned with predicting release outcomes are discussed in the earlier report (Lorei, 1964). Since that review, Johnston and McNeal (1965) found that patients whose MMPI exit profiles were judged improved over their admission profiles stay out of the hospital significantly longer than patients who did not show this improvement.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The findings of some of the more recent studies concerned with predicting release outcomes are discussed in the earlier report (Lorei, 1964). Since that review, Johnston and McNeal (1965) found that patients whose MMPI exit profiles were judged improved over their admission profiles stay out of the hospital significantly longer than patients who did not show this improvement.…”
Section: Discussionmentioning
confidence: 98%
“…Predictor Measures-Relative Lorei (1964) and Freeman and Simmons (1963) found that relatives' attitudes toward mental illness were modestly related to length of communitystay criteria. Since the OMI, the instrument the writer used in his first study, was written for hospital personnel rather than for relatives, a 60-item Likert-type opinion questionnaire was written that dealt more specifically with issues likely to be of concern to relatives of returning patients.…”
Section: Predictor Measures-patientmentioning
confidence: 99%
See 1 more Smart Citation
“…For the code of the CPI scales, see Table 8. bThe assumption that Wb assesses denial of one's emotions may help to resolve the apparent contradiction between findings that show that high scorers on Wb are healthier than low scorers (Canter, 1963;Goodstein, Crites, Heilbrun, & Rempel, 1961;Gough, 1969b) and findings that show no difference in mental health between high and low scorers (Lorei, 1964;Stewart, 1962). Megargee (1972, p. 52) mentioned Gough's suggestion that Wb assesses a state rather than a trait but was skeptical about it.…”
mentioning
confidence: 99%
“…Specifically, an atmosphere high in authoritarian restrictiveness was found to be negatively associated with the number of in‐community days, while other atmosphere types were positively related to the same criterion. In still another study, relatives' opinions about mental illness were shown to be correlated with the success or failure of psychiatric patients to achieve a 9‐month uninterrupted community stay following hospital release (5). Low scores for authoritarian and restrictive attitudes and high scores for benevolent attitudes were significantly related to success.…”
mentioning
confidence: 99%